Evidence for Intergalactic Absorption in the TEV Gamma-Ray Spectrum of Markarian 501 - Konopelko, Alexander K.; Kirk, John G.; Stecker, Floyd W.; Mastichiadis, Apostolos (1999)
The recent High-Energy Gamma-Ray Array (HEGRA) observations of the blazar Mrk 501 show strong curvature in the very high energy γ-ray spectrum. Applying the γ-ray opacity derived from an empirically based model of the intergalactic infrared background radiation field to these observations, we find that the intrinsic spectrum of this source is consistent with a power law: dNγ/dE~E-α, with α=2.00+/-0.03 over the range 500 GeV-20 TeV. Within current synchrotron self-Compton scenarios, the fact that the TeV spectral energy distribution of Mrk 501 does not vary with luminosity, combined with the correlated, spectrally variable emission in X-rays as observed by the BeppoSAX and Rossi X-Ray Timing Explorer instruments, also independently implies that the intrinsic spectrum must be close to α=2. Thus, the observed curvature in the spectrum is most easily understood as resulting from intergalactic absorption.
Keywords: Astrophysics; galaxies: active; Galaxies: BL Lacertae Objects: Individual: Name: Markarian 501; gamma rays: theory